2017
DOI: 10.1080/14760584.2017.1360771
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review about Streptococcus Pneumoniae serotype distribution in children in mainland of China before the PCV13 was licensed

Abstract: Streptococcus pneumoniae (S. pneumoniae) is a major pathogen of infectious diseases in children. Surveillance of the distribution of pneumococcus serotypes is important for immunization strategies of pneumococcal polysaccharide conjugate vaccines (PCVs). Areas covered: This article is a systematic review of studies conducted from 2006 to 2016 that document serotypes of S. pneumoniae isolated from children less than 14 years old in the mainland of China. A total of 40 studies were included in this review. Serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
6
19
0
Order By: Relevance
“…8 Thus, the most common serotypes causing IPD may vary slightly across geographic regions. Among the strains isolated from children aged younger than 18 years, serotypes 19F, 19A and 23F were the most common serotypes, results that were similar to those of Lyu et al 7 In addition, serotype 23F, 14 and 6B were important causes of either PD or IPD in children. This finding was consistent with the results from Western Europe and the USA that serogroups 14, 23, and 6 were common serogroups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…8 Thus, the most common serotypes causing IPD may vary slightly across geographic regions. Among the strains isolated from children aged younger than 18 years, serotypes 19F, 19A and 23F were the most common serotypes, results that were similar to those of Lyu et al 7 In addition, serotype 23F, 14 and 6B were important causes of either PD or IPD in children. This finding was consistent with the results from Western Europe and the USA that serogroups 14, 23, and 6 were common serogroups.…”
Section: Discussionsupporting
confidence: 85%
“…For all of the isolates included in our study, the coverage rates of PCV13 and PPSV23 were significantly higher than those of PCV10, with no significant differences between PCV13 and PPSV23, a finding that was s consistent with other study findings in China. 7,12 Although the number of serotypes in PPSV23 was more than that in PCV13, the serotype coverage of PPSV23 was slightly lower than that of PCV13, potentially due to the lack of serotype 6A in PPSV23 and the contribution of serotype 6A is higher than the combined contribution of the 11 serotypes unique to PPSV23. PCV13 has higher coverage compared with PCV7, 13 and the additional serotypes 1, 5, 7F, 3, 6A and 19A, especially for serotype 19A, account for a large proportion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because GtfA, GtfB, and PsrP are not present in about 50% of clinical iso-lates of S. pneumoniae, a PsrP-SecY2A2 island is not essential for S. pneumoniae growth. Nine serotypes were identified in 91 clinical isolates and the most frequent serotypes were 19F, 19A, 6A/B, and 23F, similar to the recently reported findings (12). The highest prevalence of PsrP was found in serotype 14, whereas no PsrP-positive isolate was found in serotypes 1 and 3 in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Mutations of GtfA, including N98A, E244A, E332A and S403A, block the glycosylation of PsrP (2,10). To date, 94 S. pneumoniae serotypes have been found (11)(12)(13)(14). Previous studies showed that PsrP was only detected in 51.7% of invasive S. pneumoniae isolates and in 48.3% of carrier S. pneumoniae isolates (15), thus, we sought to examine if the presence of the PsrP-SecY2A2 island is associated to a certain serotype of S. pneumoniae, or if GtfA and GtfB are conserved among these S. pneumoniae isolates and involved in the glycosylation of PsrP via the formation of the glycosyltransferase complex GtfA-GtfB.…”
Section: Introductionmentioning
confidence: 99%